Matières à scandales ou matières recyclables ?Trois décennies de débats sur la libération des déchets nucléaires de très faible activité (TFA) - Emmanuel Martinais (VertigO, 2021)
This article deals with very low-level radioactive waste produced in huge volumes by decommissioning nuclear installations. These bulky but not so dangerous materials are the subject of substantial professional debates. Some actors support confinement in secure storage centers for all of them, and others recommend recycling or evacuation to conventional landfills. Based on a field survey on the French case, the paper proposes an overview of these debates and their consequences on national regulation. Three periods are successively examined: first, the genesis of this national regulation in the 1990s, which led to the renunciation of the possibilities of recycling and trivialization; second, the increase in decommissioning in the 2000s, which calls into question the initial choice of generalized confinement; third, the study of two recycling channels in the 2010s, which shows the difficulties of recycling to compete with the solution of generalized confinement.very low-level radioactive waste, decommissioning, clearance levels, generalized confinement, recycling